Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.heliyon.2021.e07273
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of a sub-population of cancer stem cells from two triple-negative breast tumour cell lines

Abstract: Biological characteristics of a subpopulation of cancer stem cells from two triple-negative breast tumour cell lines, HELIYON,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Cancer stem cells have the ability to self-renew, differentiate, and initiate tumor growth and metastasis. The identification of markers that are specific to CSCs is important for understanding their biology and developing targeted therapies [ 4 , 14 ]. Cancer stem cells (CSCs) are a crucial subpopulation within tumors, known for their ability to self-renew, differentiate, and initiate tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer stem cells have the ability to self-renew, differentiate, and initiate tumor growth and metastasis. The identification of markers that are specific to CSCs is important for understanding their biology and developing targeted therapies [ 4 , 14 ]. Cancer stem cells (CSCs) are a crucial subpopulation within tumors, known for their ability to self-renew, differentiate, and initiate tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism contributing to treatment survival and disease relapse is the presence of cancer stem cells (CSCs) within the tumor tissue. These cells possess pluripotent properties [ 4 ]. CSCs are defined as a subpopulation of tumor cells with the capacity for self-renewal and differentiation to drive the initiation, progression, metastasis, and recurrence of tumors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the obtained results, it is reasonable to conclude that carboplatin did not operate properly in the first 24 h of the cell viability test; the explanation for this may be found in the mechanism of carboplatin action. Because in the mentioned test, a fixed number of cells are seeded, which by inhibiting their proliferation in the first 24 h after sticking (something equivalent to half the rate of duplication of MDA-MB-231 cells in ~ 42 h) 53 cannot be expected to have a significant effect. However, carboplatin has a greater effect in 48 h, which is nearly similar to the rate of cell duplication (~ 42 h).…”
Section: Discussionmentioning
confidence: 99%
“…PCSCs are distinguished from PCa cells by their ability to differentiate uncontrollably, self-renewability, stemness, and quiescence. On the other hand, cancer stem cells (CSCs) divide symmetrically to produce a clone of two CSCs or asymmetrically to produce one CSC and another differentiated form that becomes part of the tumor. , Although evidence suggests the origin of CSCs, its ability to initiate tumors, or the degree to which CSCs can influence tumorigenesis is uncertain, and studies have shown that CSCs are involved in tumor relapse, migration, and resistance toward therapy. In fact, the plasticity of PCSCs essentially plays a bigger part in bone metastases of PCa. , …”
Section: Introductionmentioning
confidence: 99%